Emerging trends in education, language studies and cross-cultural communication - Erda Wati Bakar; Emily Abd Rahman (Penerbit Universiti Pertahanan Nasional Malaysia, 2021)
This book should be treated as a comprehensive and accesible guide to prominent debates and trends in the expanding fields of Education, Language Studies and, Cross-cultural communication.